The impact of socio-ecological transition on employment structure and patterns in the context of (non) rural regions - Boris Najman; Alexander Neumann; Izabela Styczynska (Center for Social and Economic Research (CASE), 2013)
This paper focuses on emerging labour patterns within the Socio-Ecological Transition (SET), with particular attention paid to the effects of urbanisation. Based on the European Labour Force Survey (ELFS), the authors mobilize micro-econometric approaches in order to understand three major employment patterns: job mobility (between unemployment, inactivity, and employment), the desire to change jobs, and underemployment (i.e. part time jobs) in the European Union. The results show that the urbanization transition might express some positive effects on the labour market in the medium-term for several reasons. The employment rate has slightly decreased in all types of regions, yet it remains higher in urban settlements. Urban settlements offer more job opportunities and more part-time employment options. However, cyclical shocks tend to have a higher impact on urban areas when compared to rural areas. This means higher chances for employment in urban settlements during a boom and more job losses during a slow-down (causing less security on the labour market).
Keywords: J21; R11; 330; Employment Structure and Patterns; Urbanisation; Socio-Ecological Transformation; Erwerbstätigkeit; Arbeitsmobilität; Teilzeitarbeit; Stadt; Ländlicher Raum; Urbanisierung; Nachhaltige Entwicklung; EU-Staaten